Compressive strengths of water treatment sludge-fly ash geopolymer at various compression energies - C. Suksiripattanapong; T. Srijumpa; S. Horpibulsuk; P. Sukmak; A. Arulrajah; Y.J. Du (International Association of Lowland Technology, 2015)
Sludge-fly ash geopolymer is a green material, which does not require cement as a cementitious binder. Sludge and fly ash (FA) are both by-products from Bang Khen water treatment plants and Mae Moh power plants, respectively. A liquid alkaline activator, L is a mixture of sodium silicate solution (Na2SiO3) and sodium hydroxide solution (NaOH). This article investigates the influence of compression energy (E) on the Unconfined Compressive Strength (UCS) of a novel sludge-fly ash geopolymer. The optimal liquid alkaline activator (L) content, sodium silicate solution to sodium hydroxide solution ratio (Na2SiO3/NaOH), heat temperature (T) and heat duration (D), providing the maximum UCS for each E is also investigated. Test results indicate that the optimal L/FA ratio decreases as E increases. The optimal L/FA ratios for E = 592.5, 1346.6 and 2693.3 kJ/m3 are 1.5, 1.4 and 1.3, respectively. The Na2SiO3/NaOH ratio of 80:20 is considered as optimal for all E tested. The UCS of sludge-FA geopolymer at all E values tested increases with an increase of heat duration until a heat duration of 72 hours, after which the UCS becomes almost constant. The heat temperature accelerates the geopolymerization reaction and therefore enhances the strength. However, overheating results in micro-cracks in the samples due to the loss of moisture. As such, the optimal temperature is controlled by liquid content; the higher L/FA results in the lower optimal heat temperature. Since the optimal L/FA ratio decreases as E increases, the optimal T subsequently decreases with an increase in E; i.e., its values are 75, 85 and 95 oC for E = 2693.3, 1346.6 and 592.5 kJ/m3, respectively. The maximum UCS values of sludge-FA geopolymer at optimal ingredient and heat condition are 20, 18 and 16 MPa for E = 2693.3, 1346.6 and 592.5 kJ/m3, respectively, which meet the strength requirement of bearing masonry units as specified by the Thailand Industrial Standard (TIS).